Building and constructive materials as an urban geological resource in Trikala prefecture - Bathrellos, G. D.; Skilodimou, H. D.; Chrysanthaki, I. (Bulletin of the Geological Society of Greece, 2007)
In this study were investigated the building and constrictive materials in the settlements of Trikala prefecture. These settlements have a long history of housing with buildings constructed by a variety rock types from very different geological settings. In the modern human and urban constructions are used mainly materials that have been suffered secondary (industrial) elaboration, such as cement, asphalt, glass and building iron. In older constructions (streets, homes, stables, bridges, etc) the man used materials, which the most came from local excavations. The used domestic natural materials in the human older constructions are attractive, as well as suited with the physical environment. On the contrary, the modern materials are usually strange and unsuitable to natural environment. The usage of rich and various geological resources in the urban regions present perhaps the best occasion for achieving the connection between the human culture and urban growth with the geology